设 $k > 1$, 则级数 $\sum_{n=1}^{\infty} \frac{(-1)^n}{\sqrt{k n}+(-1)^n}$ 的敛散性为
$ \text{A.} $ 绝对收敛. $ \text{B.} $ 条件收敛. $ \text{C.} $ 发散. $ \text{D.} $ 收敛性与 $k$ 的取值有关.
【答案】 C

【解析】 $\frac{(-1)^n}{\sqrt{k n}+(-1)^n}=\frac{(-1)^n\left[\sqrt{k n}-(-1)^n\right]}{k n-1}=\frac{(-1)^n \sqrt{k n}}{k n-1}-\frac{1}{k n-1}$,
令 $u_n=\frac{\sqrt{k n}}{k n-1}$, 则 $\lim _{n \rightarrow \infty} u_n=0$, 且
$$
u_{n+1}-u_n=\frac{\sqrt{k(n+1)}}{k(n+1)-1}-\frac{\sqrt{k n}}{k n-1}=\sqrt{k} \cdot \frac{[k \sqrt{n(n+1)}+1](\sqrt{n}-\sqrt{n+1})}{[k(n+1)-1](k n-1)} < 0,
$$
即 $u_{n+1} < u_n$,
由莱布尼茨定理知, 交错级数 $\sum_{n=1}^{\infty} \frac{(-1)^n \sqrt{k n}}{k n-1}$ 收玫, 而级数 $\sum_{n=1}^{\infty} \frac{1}{k n-1}$ 发散, 所以原级数发散.
故应选 (C).
系统推荐